Analiza hermeneutyczna narracji autobiograficznych w badaniach noetycznego poziomu rozwoju człowieka = Hermeneutic analysis of autobiographical narrations in the research on noetic level of human development - Mróz, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Hermeneutics has numerous meanings. One of them is the understanding of it as the art of interpreting spoken or written text. It has also gained the status of methodology within humanistic science. The applications of hermeneutics interpretation to analyse philosophy or literary texts is widely known. The question is whether it may be applied in the research carried out on the ground of empirical science about a human; namely psychology.
Keywords: hermeneutyka; psychologia; narracja autobiograficzna; rozwój człowieka